PENGARUH BEBAN KERJA TERHADAP STRES KERJA PADA ANGGOTA POLISI BAGIAN RENMIN POLDA KALTENG - Prima Azmi; Rizqi Amalia Aprianty; Julaibib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the role of workload in predicting work stress among police officers in the Renmin Division of the Central Kalimantan Regional Police. The study employed a quantitative approach with a correlational design. The participants consisted of 112 police officers selected using convenience sampling. Data were collected online using a workload scale and a work stress scale. The data were analyzed using simple linear regression with a bootstrap technique involving 10,000 replications through JASP. The results of the simple linear regression analysis with bootstrap showed that workload positively and significantly predicted work stress, with an unstandardized regression coefficient of b = 1.294, 95% CI [0.997, 1.495], and p < 0.001. The R² value of 0.484 indicated that workload explained 48.4% of the variance in work stress, while the remaining 51.6% was explained by other factors outside the research model. Thus, the higher the workload perceived by police officers, the higher the level of work stress they experienced. These findings may serve as a consideration for the organization in managing task distribution, setting work priorities, and maintaining officers’ psychological well-being so that they can perform their duties optimally..